How do professional tennis players move? The perceptions of coaches and strength and conditioning experts - Giles, B.; Peeling, P.; Dawson, B.; Reid, M. (Journal of Sports Sciences, 2019)
The purpose of this study was to explore the processes associated with successful on-court movement in professional tennis. To date, research has only provided generalised insight into the physical demands of tennis movement and the requisite physical skills. Data were collected through semi-structured interviews with 15 international tennis and/or strength and conditioning coaches involved in the development of tennis-specific movement in professional men`s and women`s tennis. A descriptive, qualitative approach was adopted, with interviews transcribed verbatim and analysed using an inductive to deductive thematic analysis. The highlighted ideas and concepts enabled the dynamic construction of higher-order themes representative of "good" tennis movers, alongside the conceptual development of a common movement "goal" or "outcome". The established higher-order themes portrayed three "styles" of "good" movers in modern professional tennis: those who were "fast" around the court, those who "read the play" well, and those who were "efficient" in their movement. The established themes provide a framework for interpreting and categorising the movement of professional tennis players as well as its underpinning skill.